The Influence of Job Demand and Family Time on Driver's Effort with Burnout as Mediator (Empirical Study of Drivers of Online Ojek Provider Company) - Talita Rizky Amalia; Muhammad Irfan Syaebani (Cakrawala Repositori IMWI, 2023)
Numerous studies seek to comprehend the emergences and processes of job performance, but they overlook the input of performance, which is effort. This research is not only headed in that direction, but also concentrates on exploring and analyzing the variables of job demand and work-family balance in relation to burnout and how it affects Goride Driver from Gojek's work effort. This research involved 229 Goride drivers from Gojek in Jabodetabek area. Covariance Based Structural Equation Modeling (CB-SEM) was used to examine the data received from a 6-point Likert scale online survey. This study found that job demand negatively associated with work-family balance, but associated positively to burnout. Work-family associated positively with effort. Job demand and burnout associated negatively with effort. Burnout does not mediate the relationship of job demand and work-family balance to effort. This finding provides an explanation for variables such as job demands, work-family balance, burnout, and effort, and how they interact in the gig economy among gig workers such as the Goride driver.